Production Based Training on Agro Industry Expertise Course to Improve Student’s Competencies in Food Diversification based on Local Resources - Handayani, Sri; Handayani, Mustika Nuramalia; Cakrawati, Dewi (Faculty of Technological and Vocational Education-Universitas Pendidikan Indonesia, 2016)
The research approach was developmental research for improving, implementing and evaluating a production based learning (PBL on subject of Technology Processing of Animal Product at Study Program of Education on Agroindustry Technology, Universitas Pendidikan Indonesia. Syntax of Production based learning are (1) Explanation of the objectives and competencies to be achieved; (2) Explanation of course material; (3) the making of group where each member of the group is divided according to the division in the company; (4) Preparation of company profile by each group; (5) SOP for each part by each group; (6) Practical manufacture of processed products by each group - syntax 1 to 6 can be repeated according to the number of products produced by each group, each group member should play different role in every different , so that every group member possessed the skill in every work part of producing a product; (7) Naming the product and work report by each student. The result showed that there was improvement in students’ knowledge seen from student’s test score. The result also showed that there was improvement in student’s skill seen by performance assessment.